Perbandingan Konsep Pembatalan Putusan Arbitrase Di Beberapa Negara - Nurhayati, Yati (Jurnal Ius Constituendum, 2022)
This study aims to dissect the concept of annulment of arbitral awards in several countries. Arbitration disputes are one of the options in resolving business disputes that are used in various countries in the world, one of which is Indonesia. Arbitration, both national and international, has a very important role in the business world which continues to develop, especially in the digital era. However, the arbitration award which has a final and binding nature still has a denial effort through the annulment of the award. In Indonesia, the provisions for the cancellation of arbitration are regulated in Article 70 of the Arbitration Law which has changed from the provisions before the birth of the Arbitration Law. This study uses a normative research method (comparative descriptive) which focuses on comparing the concept of annulment of arbitral awards in several countries in accordance with the laws and regulations in force in each country, not only discussing the rejection of the implementation of arbitral awards in comparison of two countries, the conditions for the cancellation of arbitral awards. national or international arbitral award. The results of the study showed that although arbitration applies in almost many countries, the provisions for the cancellation of arbitration awards in several countries are different.  Penelitian ini bertujuan membedah konsep pembatalan putusan arbitrase dibeberapa negara. Sengketa arbitrase menjadi salah satu pilihan dalam penyelesaian sengketa bisnis yang digunakan diberbagai negara di dunia salah satunya di Indonesia. Arbitrase baik nasional maupun internasional memiliki peran yang sangat penting dalam dunia bisnis yang terus mengalami perkembangan terutama di era digital. Namun putusan arbitrase yang memiliki sifat final dan binding pun tetap memiliki upaya penyangkalan melalui pembatalan putusan. Di Indonesia ketentuan pembatalan arbitrase diatur dalam Pasal 70 UU Arbitrase yang mengalami perubahan dari ketentuan sebelum lahirnya UU arbitrase. Penelitian ini menggunakan metode penelitian normatif (deskriptif perbandingan) yang berfokus pada perbandingan konsep pembatalan putusan arbitrase di beberapa negara sesuai dengan peraturan perundang-undanagn yang berlaku di tiap negara, tidaka hanya membahas tentang penolakan pelaksanaan putusan arbitrase perbandingan dua negara saja, syarat pembatalan putusan arbitrase nasional atau pembatalan putusan arbitrase internasional. Hasil penelitian didapatkan bahwa meskipun arbitrase berlaku di hampir banyak negara namun ketentuan pembatalan putusan arbitrase dibeberapa negara berbeda-beda.